Water-based inks and laminates

A water-based ink with a self-crosslinked (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin, along with a curing agent, addresses the challenges of adhesion and resistance in water-based inks, enabling high pigment concentration and excellent film properties in a single printing layer.

JP7665079B1Inactive Publication Date: 2025-04-18DIC GRAPHICS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024084026
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water-based inks struggle to achieve excellent adhesion, blocking resistance, water friction resistance, and alcohol resistance, while also maintaining high pigment concentration without deteriorating physical coating properties.

Method used

The development of a water-based ink containing a self-crosslinked (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin, along with a curing agent, which enhances film properties and allows for single-layer printing with high pigment concentration.

Benefits of technology

The ink achieves excellent adhesion, blocking resistance, water friction resistance, and alcohol resistance, even with high pigment concentrations, resulting in improved aesthetic and durability properties in a single printing layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665079000001
    Figure 0007665079000001
  • Figure 0007665079000002
    Figure 0007665079000002
  • Figure 0007665079000003
    Figure 0007665079000003
Patent Text Reader

Abstract

To provide a water-based ink capable of giving a film excellent in adhesion, resistance to blocking between films, resistance to water friction, and resistance to alcohol, and a laminate using the same. [Solution] A laminate comprising: a binder resin, a curing agent, and an aqueous solvent, the binder resin being a self-crosslinking (meth)acrylic resin emulsion, an aqueous ink containing an alkali-soluble water-soluble resin; a substrate; and a printed layer provided on the substrate, the printed layer being a printed layer of the aqueous ink.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-based ink and a laminate. [Background technology]

[0002] Gravure inks and flexographic inks are widely used to impart beauty and functionality to printed flexible packaging films.

[0003] Specifically, for example, when packaging products, these gravure inks and flexographic inks are printed on the front side (the side that does not come into contact with the product being packaged) of the base plastic film for decoration and surface protection, and printed materials with a simple structure (called a surface printing method) are used in which the back side (the side that comes into contact with the product being packaged) is not printed.

[0004] In the case of labels wrapped around PET bottles or shrink labels, a top coat varnish is generally printed on the outer surface to provide a scratch prevention function for the film, and a decorative printing layer and a varnish layer to provide blocking prevention for the PET bottle are provided on the inner surface. The ink and top coat varnish used in the above-mentioned surface printing are directly exposed to the outside and come into direct contact with other members, and therefore require film properties that are strong enough to withstand handling of the product, etc. In addition, the quality of the printed design on the soft packaging film can have a large impact on the quality of the contents, so the decorative printing layer must have high image reproducibility that can accommodate sophisticated designs that are conscious of aesthetic appeal.

[0005] In recent years, in response to the trend toward a shift away from petroleum resources, in addition to considerations of occupational safety and health, as well as flammability and explosiveness, and based on the viewpoint of sustainability against the backdrop of the worsening of air pollution by VOCs and the global expansion of global warming, the spread of so-called water-based inks, in which the organic solvent in the ink is replaced with water, is expected. Under these circumstances, various studies are being conducted on water-based inks that can also be used as inks for surface printing and topcoat varnishes (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 07441356 Summary of the Invention [Problem to be solved by the invention]

[0007] Here, the ink film is required to have various film properties (blocking resistance between films, alcohol resistance, water friction resistance, etc.) in addition to adhesion to the substrate. Therefore, improvements that satisfy all of these requirements are required for water-based inks. In addition, since decorative printing layers contain pigments, it is difficult to provide excellent printing suitability in addition to various coating properties. For example, when providing a white printing layer on a transparent film, a white printing layer with sufficient white density has been conventionally obtained by printing twice with white ink. However, this method requires more work since it requires printing twice, and two printing units must be used with the white ink, making it difficult to add special colors and limiting the reproducible color gamut. In order to ensure white density with one printing, it is necessary to increase the concentration of the white pigment in the ink, but there is a problem that increasing the pigment concentration tends to deteriorate various coating properties.

[0008] Therefore, an object of the present invention is to provide a water-based ink which can give a film having excellent adhesion, resistance to blocking between films, resistance to water friction, and resistance to alcohol. Another object of the present invention is to provide a laminate having, as a film, an ink layer that has excellent adhesion, resistance to blocking between films, resistance to water friction, and resistance to alcohol. [Means for solving the problem]

[0009] That is, the present invention relates to an aqueous ink containing a binder resin, a curing agent, and an aqueous solvent, the binder resin containing a self-crosslinking (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin.

[0010] The present invention also relates to a laminate comprising a substrate and a printed layer provided on the substrate, the printed layer containing a binder resin, a curing agent, and an aqueous solvent, the binder resin being a printed layer of an aqueous ink containing a self-crosslinking (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin. Effect of the Invention

[0011] According to the present invention, it is possible to provide a water-based ink which can give a film having excellent adhesion, resistance to blocking between films, resistance to water friction, and resistance to alcohol. Furthermore, according to the present invention, it is possible to provide a laminate having an aqueous ink layer as a coating, which can provide a coating having excellent adhesion, resistance to blocking between coatings, resistance to water friction, and resistance to alcohol. The aqueous ink of the present invention can provide a coating that is excellent in adhesion, resistance to blocking between coatings, resistance to water friction, and resistance to alcohol, even when the aqueous ink has a high pigment concentration. Therefore, the aqueous ink of the present invention and a laminate having the aqueous ink layer of the present invention as a coating can provide an ink layer with excellent cosmetic properties in a single printing run. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following provides a detailed description of an embodiment of the present invention (hereinafter, sometimes referred to as the "present embodiment"); however, the present invention is not limited to the following description, and can be implemented in various modified forms within the scope of its gist.

[0013] (Water-based ink) The water-based ink of the present invention contains a binder resin, a curing agent, and an aqueous solvent, and the binder resin is characterized in that it contains a self-crosslinking (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, and "(meth)acrylate" means acrylate and / or methacrylate.

[0014] <Binder resin> The water-based ink of the present invention contains a self-crosslinking (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin as a binder resin.

[0015] (Self-crosslinking (meth)acrylic resin emulsion) The self-crosslinking (meth)acrylic resin emulsion used in the present invention may be a publicly known and available self-crosslinking (meth)acrylic resin emulsion. The self-crosslinking (meth)acrylic resin emulsion may be a single type or a combination of two or more types.

[0016] The (meth)acrylic resin contained in the self-crosslinking (meth)acrylic resin emulsion is not particularly limited, and examples thereof include homopolymerization or copolymerization of (meth)acrylate, and copolymerization of vinyl monomer copolymerizable with (meth)acrylate. In addition, it is preferable that the copolymer has an acid value in order to impart water dispersibility and water solubility. Specifically, examples of resins having a structural unit derived from a (meth)acrylic acid ester monomer include acrylic resin, styrene acrylic resin, polyester-acrylic resin, urethane-acrylic resin, vinyl chloride-vinyl acetate copolymer-acrylic resin, silicone-acrylic resin, acrylamide resin, and epoxy-acrylic resin. In other words, the (meth)acrylic resin refers to a resin obtained by (co)polymerizing a (meth)acrylic acid ester as an essential monomer together with other polymerizable unsaturated group-containing compounds as required.

[0017] Examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-pentafluoropropyl (meth)acrylate, and perfluoro. Examples of the (meth)acrylate include cyclohexyl (meth)acrylate, glycidyl (meth)acrylate, allyl glycidyl ether, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polyethylene glycol mono (meth)acrylate, (meth)acrylamide, N-monoalkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide, N-methylol (meth)acrylamide, N-isopropoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, N-isobutoxymethyl (meth)acrylamide, 2-aziridinylethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, acrolein, diacetone (meth)acrylamide, and acetoacetoxyethyl (meth)acrylate. The (meth)acrylate may be one type alone or two or more types in combination.

[0018] Examples of the polymerizable unsaturated group-containing compound include vinyl monomers such as vinyl acetate, vinyl propionate, vinyl versatate, methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, (meth)acrylonitrile, styrene, α-methylstyrene, divinylstyrene, isoprene, chloroprene, butadiene, ethylene, tetrafluoroethylene, vinylidene fluoride, and N-vinylpyrrolidone. The polymerizable unsaturated group-containing compound may be a single type or a combination of two or more types.

[0019] Furthermore, for the purpose of introducing one or more types of acidic groups selected from the group consisting of a carboxyl group and a carboxylate group in which the carboxyl group has been neutralized with a basic compound, a copolymer having an acid value can be obtained by copolymerizing a (meth)acrylic monomer having a carboxyl group, such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, β-(meth)acryloyloxyethyl hydrogen succinate, or β-(meth)acryloyloxyethyl hydrogen phthalate. When an acidic group is introduced, it is preferable to appropriately adjust the amount of monomer so that the acid value falls within a desired range, as will be described in detail later.

[0020] The self-crosslinking (meth)acrylic resin emulsion contains a self-crosslinking component, such as an isocyanate compound, an epoxy compound, an amine compound, a melamine compound, an aziridine compound, a hydrazine compound, an aldehyde compound, or an oxazoline compound. Among these, a hydrazine compound is preferred, and an example of the hydrazine compound is adipic acid dihydrazide. The content of the self-crosslinking component is preferably 0.1 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the acrylic emulsion solution in order to improve the storage stability of the self-crosslinking (meth)acrylic resin emulsion, and more preferably 0.3 parts by mass or more and 3 parts by mass or less. In addition, the (meth)acrylic resin contains a functional group that reacts with the self-crosslinking component. Therefore, it is necessary to produce the resin by including a polymerizable unsaturated monomer that reacts with the self-crosslinking component. Examples of such polymerizable unsaturated monomers include radical polymerizable unsaturated monomers containing carbonyl groups such as diacetone (meth)acrylamide, diacetone (meth)acrylate, acetonyl (meth)acrylate, vinyl alkyl ketones, acrolein, formyl styrene, (meth)acrylic acid, and alkanal (meth)acrylates, radical polymerizable unsaturated monomers containing carboxyl groups, and radical polymerizable unsaturated monomers containing hydroxyl groups. Among these, diacetone (meth)acrylamide and diacetone (meth)acrylate are preferred. The self-crosslinking (meth)acrylic resin emulsion may, for example, contain both carbonyl and amine functional groups, and thus have the self-reactive functionality that allows them to react with each other.

[0021] The self-crosslinking (meth)acrylic resin emulsion may preferably be an emulsion that forms a core-shell type. The core-shell type emulsion refers to a state in which a first polymer is dispersed in an aqueous medium by a second polymer, and usually, the second polymer is present at the outermost part of the resin particles to form a shell part, and a part or all of the first polymer forms a core part. The polymer that forms the shell part is hydrophilic, while the polymer that forms the core part is hydrophobic. The hydrophilic shell part maintains the dispersion, while the hydrophobic core part provides a reactive site for crosslinking, so that it is preferable that the polymer that forms the core part contains a functional group that reacts with the self-crosslinking component.

[0022] The (meth)acrylic resin can be produced, for example, by polymerizing various monomers in the presence of a polymerization initiator at a temperature range of 50°C to 180°C, more preferably 80°C to 150°C. Examples of the polymerization method include bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. In addition, the (meth)acrylic resin in the case of being a copolymer may be a random copolymer, a block copolymer, a graft copolymer, and the like, from the viewpoint of its polymerization mode. When the (meth)acrylic resin is obtained by the above-mentioned bulk polymerization or solution polymerization method, the (meth)acrylic resin having an acidic group introduced therein can be neutralized with a neutralizing agent such as an alkali after polymerization, and the solvent can be replaced with an aqueous medium to form an aqueous emulsion.

[0023] The glass transition temperature (Tg) of the self-crosslinking (meth)acrylic resin emulsion is preferably in the range of -30°C to 60°C, and more preferably in the range of -10°C to 50°C.

[0024] In the present invention, the glass transition temperature (Tg) refers to the so-called calculated glass transition temperature, and refers to a value calculated by the following method. (Formula 1) 1 / Tg(K)=(W1 / T1)+(W2 / T2)+...(Wn / Tn) (Equation 2) Tg(℃)=Tg(K)-273 In formula 1, W1, W2, ...Wn represent the mass% of each monomer relative to the total mass of the monomers used in the production of the polymer, and T1, T2, ...Tn represent the glass transition temperature (K) of the homopolymer of each monomer. The values ​​of T1, T2, ...Tn are those listed in Polymer Handbook (Fourth Edition, edited by J. Brandrup, EH Immergut, and EA Grulke). In addition, the glass transition temperature of the homopolymer of each monomer that is not listed in the Polymer Handbook was measured using a differential scanning calorimeter "DSCQ-100" (manufactured by TA Instrument) in accordance with a method conforming to JIS K7121. Specifically, the polymer was evacuated to completely remove the solvent, and the heat change was measured in the range of -100°C to +200°C at a heating rate of 20°C / min. The glass transition temperature was determined as the point where a straight line equidistant in the vertical direction from the extended straight line of each baseline intersected with the curve of the stepwise change portion of the glass transition.

[0025] The acid value (also referred to as "AV") of the self-crosslinking (meth)acrylic resin emulsion is preferably 0 mgKOH / g to 100 mgKOH / g. This range is preferable because it allows the effects of the present invention to be maximized. The acid value of the (meth)acrylic resin (A) is more preferably 15 mgKOH / g or more, and more preferably 60 mgKOH / g or less, and even more preferably 40 mgKOH / g or less. In the present invention, the acid value refers to the number of milligrams of potassium hydroxide required to neutralize the acidic components contained in 1 g of resin.

[0026] In the present invention, the self-crosslinking (meth)acrylic resin emulsion is preferably an acrylic resin (i.e., a resin obtained by polymerizing substantially only (meth)acrylic acid ester monomers) or a styrene-acrylic resin (i.e., a resin obtained by copolymerizing a styrene monomer and a (meth)acrylic acid ester monomer) from the viewpoint of improving adhesion to the substrate and strength of the coating, and is more preferably a styrene-acrylic resin.

[0027] (Alkali-soluble water-soluble resin) The alkali-soluble water-soluble resin used in the present invention is not particularly limited, and any publicly available alkali-soluble water-soluble resin can be used. Among them, it is preferable to use a (meth)acrylic resin from the viewpoint of compatibility with the self-crosslinking (meth)acrylic resin emulsion. The (meth)acrylic resin can be the same resin as that used in the aqueous (meth)acrylic emulsion. The alkali-soluble water-soluble resin may be used alone or in combination of two or more kinds. The aqueous ink of the present invention contains an alkali-soluble water-soluble resin, which improves the ink's stability over time and improves the pigment dispersibility of ink containing a large amount of pigment. Furthermore, the ink can be easily washed off from a printing machine using a synthetic detergent after printing.

[0028] In the present invention, the alkali-soluble water-soluble resin is preferably an acrylic resin (i.e., a resin obtained by polymerizing substantially only (meth)acrylic acid ester monomers) or a styrene-acrylic resin (i.e., a resin obtained by copolymerizing a styrene monomer and a (meth)acrylic acid ester monomer), and more preferably a styrene-acrylic resin.

[0029] In the present invention, the (meth)acrylic resin, which is an alkali-soluble water-soluble resin, may be reacted with a self-crosslinking component. That is, the (meth)acrylic resin may be a self-crosslinking type. Examples of the self-crosslinking component include an isocyanate compound, an epoxy compound, an amine compound, a melamine compound, a hydrazine compound, an aldehyde compound, and an oxazoline compound. However, from the viewpoint of improving the ink stability over time, the ink washability, and the pigment dispersibility, it is preferable that the alkali-soluble water-soluble resin is a resin that is not a self-crosslinking type.

[0030] The glass transition temperature (Tg) of the alkali-soluble water-soluble resin is preferably in the range of 10° C. to 140° C. from the viewpoint of improving the adhesion to the substrate, blocking resistance, and water abrasion resistance. In particular, the glass transition temperature (Tg) is more preferably 20° C. or higher, further preferably 30° C. or higher, and even more preferably 50° C. or higher, and is more preferably 130° C. or lower, further preferably 120° C. or lower, and even more preferably 100° C. or lower.

[0031] The acid value of the alkali-soluble water-soluble resin is preferably 40 mgKOH / g to 250 mgKOH. This range is preferable from the viewpoint of improving pigment dispersibility, ink washability, and water abrasion resistance. In particular, the acid value is more preferably 60 mgKOH / g or more, even more preferably 100 mgKOH / g or more, even more preferably 150 mgKOH / g or more, and more preferably 250 mgKOH / g or less, even more preferably 230 mgKOH / g or less.

[0032] (mass ratio) In the present invention, the mass ratio of the non-volatile content of the self-crosslinking (meth)acrylic resin emulsion to the alkali-soluble water-soluble resin is preferably self-crosslinking (meth)acrylic resin emulsion / alkali-soluble water-soluble resin=10 / 90 to 90 / 10. By setting it in this range, pigment dispersibility, ink washability, water abrasion resistance, etc. can be maximized. Among them, the mass ratio is more preferably in the range of 20 / 80 to 85 / 15, and most preferably in the range of 30 / 70 to 80 / 20.

[0033] In the present invention, the binder resin may contain a resin other than the self-crosslinking (meth)acrylic resin emulsion and the alkali-soluble water-soluble resin. However, from the viewpoint of more effectively improving the effects of the present invention, the ratio of the self-crosslinking (meth)acrylic resin emulsion and the alkali-soluble water-soluble resin in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and also preferably 100% by mass (i.e., the binder resin is composed only of the self-crosslinking (meth)acrylic resin emulsion and the alkali-soluble water-soluble resin).

[0034] <Hardening agent> The water-based ink of the present invention contains a curing agent. Since the water-based ink of the present invention contains a self-crosslinking (meth)acrylic resin emulsion, it has excellent adhesion to a substrate and excellent film strength, but the effect of the present invention can be further improved by containing a curing agent. As the curing agent, a known one can be used, and it is preferable to use a crosslinking agent capable of reacting with a carboxy group in the binder resin. Among them, at least one crosslinking agent selected from the group consisting of an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a carbodiimide-based crosslinking agent, a chelate-based curing agent such as a titanium chelate, and an isocyanate-based crosslinking agent that can be blended in an aqueous ink is preferable, and an aziridine-based curing agent is more preferable. The content of the curing agent (solid content) in the ink is preferably from 0.05 to 10 mass % based on the total amount of the ink, and more preferably from 0.3 to 5 mass %.

[0035] (Aziridine-based curing agent) The aziridine curing agent is a compound having an aziridine group, and more specifically, for example, trimethylolpropane-tri-β-aziridinyl propionate, tetramethylolmethane-tri-β-aziridinyl propionate, trimethylolpropane-tri-β-(2-methylaziridine)propionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide), and N,N'-toluene-2,4-bis(1-aziridinecarboxamide) can be mentioned. The aziridine curing agent may be used alone or in combination of two or more kinds.

[0036] In addition, commercially available products can be used as the aziridine-based curing agent. Examples of commercially available aziridine-based curing agents include "PZ-33" manufactured by Nippon Shokubai Co., Ltd., "DZ-22E" manufactured by Nippon Shokubai Co., Ltd., "XL-706" manufactured by Stahl, and "SU-125F" manufactured by Meisei Chemical Industry Co., Ltd.

[0037] In the water-based ink of the present invention, the amount of the non-volatile content of the aziridine-based curing agent relative to 100 parts by mass of the non-volatile content of the binder resin is preferably 1.0 parts by mass or more and 35.0 parts by mass or less. The amount of the non-volatile content of the aziridine-based curing agent relative to 100 parts by mass of the non-volatile content of the binder resin is preferably 2.0 parts by mass or more, more preferably 3.0 parts by mass or more, and is preferably 30.0 parts by mass or less, more preferably 25.0 parts by mass or less.

[0038] In addition, when the binder resin and the aziridine-based hardener are used to prepare water-based inks, they are often in a state of being dispersed in a solvent. Therefore, in order to calculate the mass ratio of the nonvolatile content described above, it is important to know the NV value (Nonvolatile Content) of each of the binder resin and the aziridine-based hardener. In addition, the "non-volatile content" (NV) is generally also referred to as the "solid content."

[0039] (Water-based solvent) The aqueous solvent used in this embodiment may be water alone or an organic solvent miscible with water. Examples of the organic solvent include alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, and n-propyl alcohol; polyhydric alcohols such as propylene glycol and glycerin; ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono n-propyl ether, and ethyl carbitol. The aqueous solvent may be one type alone or two or more types in combination.

[0040] (Pigments) The water-based ink of the present invention may contain various pigments in addition to those mentioned above. From the viewpoint of materials, examples of the pigments include inorganic pigments and organic pigments, and from the viewpoint of coloring, examples of the pigments include black pigments, indigo pigments, green pigments, red pigments, purple pigments, yellow pigments, orange pigments, brown pigments, etc. When the water-based ink contains these pigments, it can be used as an ink for so-called black-and-white printing or color printing. When used as a white ink, the white pigment may be a conventionally known white pigment. Examples of the white pigment include white inorganic pigments such as titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, litbon, antimony white, and gypsum. Among the inorganic pigments, titanium oxide is particularly preferred. Titanium oxide exhibits a white color and is preferred in terms of coloring power, hiding power, alcohol resistance, and weather resistance, and from the viewpoint of printing performance, the titanium oxide is preferably treated with silica and / or alumina. The average particle size of the pigment is preferably in the range of 1 to 300 nm, and more preferably about 50 to 150 nm. The pigment is preferably contained in an amount sufficient to ensure the concentration and coloring power of the aqueous ink, that is, 1 to 60% by weight relative to the total weight of the ink composition, and 10 to 90% by weight in terms of the solid content weight ratio in the ink composition. In particular, the aqueous ink of the present invention is excellent in pigment dispersibility even in a composition containing 20% ​​by mass or more of the pigment relative to the total weight of the ink composition, and the film obtained by using the ink is excellent in adhesion, blocking resistance between films, water friction resistance, and alcohol resistance. The aqueous ink of the present invention may contain 30% by mass or more of the pigment in the aqueous ink, 40% by mass or more, or 50% by mass. Excellent effects can be obtained even in inks containing such pigments at high concentrations. Moreover, the pigments can be used alone or in combination of two or more kinds.

[0041] (Surfactant) The water-based ink of the present invention may further contain a surfactant in addition to the above. As the surfactant, an acetylene-based surfactant or an alcohol alkoxylate-based surfactant is preferable. These surfactants may be used alone or in combination of two or more.

[0042] Specific examples of acetylene surfactants include 2,5-dimethyl-3-hexyne-2,5-diol, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,5-dimethyl-1-hexyne-3-ol, 3-methyl-1-butyne-3-ol, 3-methyl-1-pentyne-3-ol, 3-hexyne-2,5-diol, 2-butyne-1,4-diol, etc. These acetylene surfactants may be used alone or in combination of two or more.

[0043] In addition, examples of commercially available acetylene-based surfactants include commercially available alkylene oxide-unmodified acetylene glycol surfactants and commercially available alkylene oxide-modified acetylene glycol surfactants. Commercially available alkylene oxide unmodified acetylene glycol surfactants include Surfynol 61, 82, and 104 (all manufactured by Air Products Co., Ltd.). Commercially available alkylene oxide-modified acetylene glycol surfactants include Surfynol 420, 440, 465, 485, TG, 2502, Dynol 604, 607 (all manufactured by Air Products Co., Ltd.); Surfynol SE, MD-20, Olfin E1004, E1010, PD-004, EXP4300, PD-501, PD-502, SPC (all manufactured by Nissin Chemical Industry Co., Ltd.); Acetylenol EH, E40, E60, E81, E100, E200 (all manufactured by Kawaken Fine Chemical Co., Ltd.); and the like. Among these, as the acetylene-based surfactant, an alkylene oxide-modified acetylene glycol-based surfactant is preferable.

[0044] Specific examples of the alcohol alkoxylate surfactant include alcohol ethoxylate and alcohol polyethoxylate. Commercially available alcohol alkoxylate surfactants include "BYK-DYNWET800" (manufactured by BYK). These alcohol alkoxylate surfactants may be used alone or in combination of two or more.

[0045] In addition to the above-mentioned surfactants, if necessary, acrylic polymer-based surfactants (e.g., "Polyflow WS-314" manufactured by Kyoeisha Chemical Co., Ltd.) and modified silicone-based surfactants (e.g., "Polyflow KL-401" manufactured by Kyoeisha Chemical Co., Ltd.) may be used.

[0046] When the aqueous ink of the present invention contains a surfactant, the total proportion of the surfactant in the total amount of the aqueous ink is preferably 0.1% by mass or more and 3.0% by mass or less. If the proportion is 0.1% by mass or more, the effect of increasing the wettability of the substrate and maintaining adhesion to the substrate can be obtained. Also, if the proportion is 3.0% by mass or less, the abrasion resistance, water abrasion resistance, and scratch resistance can be maintained well. From the same viewpoint, the proportion is more preferably 1.0% by mass or less.

[0047] (wax) The water-based ink of the present invention may further contain a wax in addition to the above. The wax is preferably a hydrocarbon wax. Specific examples of the wax include liquid paraffin, natural paraffin, synthetic paraffin, microcrystalline wax, polyethylene wax, fluorocarbon wax, ethylene-propylene copolymer wax, tetrafluoroethylene resin wax, and Fischer-Tropsch wax. These waxes may be used alone or in combination of two or more. Among these, the wax is preferably polyethylene wax.

[0048] When the water-based ink of the present invention contains wax, the total proportion of wax in the total amount of the water-based ink is preferably 0.5% by mass or more and 5.0% by mass or less. If the proportion is 0.5% by mass or more, the effect of maintaining water abrasion resistance can be obtained. Also, if the proportion is 5.0% by mass or less, adhesion to the substrate, water abrasion resistance, and blocking resistance can be maintained well.

[0049] (Other Ingredients) In addition to the above, the water-based ink of the present invention may contain appropriate amounts of other components, such as a general-purpose resin other than the above-mentioned binder resin, an extender pigment, a lubricant (oleic acid amide, stearic acid amide, erucic acid amide, etc.), a pigment dispersant, a leveling agent, an antifoaming agent (a silicone-based antifoaming agent, a non-silicone-based antifoaming agent, etc.), a plasticizer, an infrared absorbing agent, an ultraviolet absorbing agent, a fragrance, a flame retardant, etc., as necessary.

[0050] (Water-based ink manufacturing method) The method for producing the water-based ink of the present invention is not particularly limited, but for example, the water-based ink can be obtained by dispersing a mixture to which an aqueous solvent and an antifoaming agent etc. have been added, and then adding a binder resin, an aqueous solvent, an aziridine-based curing agent, and additives such as a surfactant as necessary, and stirring and mixing. For the above dispersion and stirring and mixing, a dispersing machine such as a bead mill, an Eiger mill, a sand mill, a gamma mill, or an attritor that is generally used in the production of inks for flexographic printing or gravure printing can be used.

[0051] Furthermore, the water-based ink of the present invention is preferably used for flexographic printing or gravure printing, as described below.

[0052] When the aqueous ink of the present invention is used for flexographic printing or gravure printing, that is, when the aqueous ink of the present invention is used as a flexographic ink or gravure ink, the viscosity may be 7 to 25 seconds, more preferably 10 to 20 seconds, at 25°C using Zahn Cup #4 manufactured by Rigo Co., Ltd. The surface tension of the ink at 25°C is preferably 25 to 50 mN / m. The lower the surface tension of the ink, the better the ink wettability to a substrate such as a film. However, when the surface tension is below 25 mN / m, the ink tends to spread and connect adjacent dots in halftone dots. This is likely to cause staining of the printed surface, called dot bridging. On the other hand, when the surface tension is above 50 mN / m, the ink wettability to a substrate such as a film is reduced, which is likely to cause repelling. From the same viewpoint, the surface tension of the ink at 25° C. is more preferably 33 mN / m or more, and more preferably 43 mN / m or less.

[0053] (Laminate) The laminate of the present invention includes a substrate and an ink layer provided on the substrate, the ink layer being a printed layer of the above-mentioned water-based ink. That is, the laminate of the present invention is obtained by printing the above-mentioned water-based ink on the substrate.

[0054] Examples of the substrate include thermoplastic resin film, paper, synthetic paper, steel plate, aluminum foil, wood, woven fabric, knitted fabric, nonwoven fabric, gypsum board, and wood board. Among these, the substrate is preferably paper, synthetic paper, or thermoplastic resin film. The substrate may be a combination of a plurality of the above-mentioned substrates, for example, a laminate substrate in which paper and a thermoplastic resin film are laminated, or a laminate substrate in which a thermoplastic resin film and an aluminum foil are laminated. In the case of a combination of a plurality of substrates, the lamination method is not particularly limited, and the substrate may be bonded using a general-purpose one-liquid adhesive, a two-liquid adhesive, or the like, or may be a laminate substrate in which a plurality of thermoplastic resin films are bonded by extrusion molding.

[0055] The thermoplastic resin film is not particularly limited, and examples thereof include polyamide resins such as nylon 6, nylon 66, and nylon 46; polyester resins such as polyethylene phthalate (PET), polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; biodegradable resins such as polyhydroxycarboxylic acids such as polylactic acid, and aliphatic polyester resins such as poly(ethylene succinate) and poly(butylene succinate); polyolefin resins such as polypropylene (PP) and polyethylene; polyimide resins; polyarylate resins; and films made of thermoplastic resins such as mixtures thereof, and also include laminated films made of a plurality of these. Among these, films made of polyester, polyamide, polyethylene, and polypropylene are preferred as the thermoplastic resin film.

[0056] These thermoplastic resin films may be unstretched or stretched films, and the manufacturing method is not particularly limited. The thickness of the thermoplastic resin film as a substrate is not particularly limited, but may usually be in the range of 1 to 500 μm. The surface of the thermoplastic resin film to be printed is preferably subjected to corona discharge treatment. In this case, the adhesion can be further improved. Furthermore, silica, alumina, etc. may be vapor-deposited on the surface of the thermoplastic resin film to be printed, and a gas barrier coating layer such as an oxygen gas barrier layer may be laminated thereon.

[0057] In order to maximize the effects of the present invention, it is preferable to use a substrate that is a constituent material of the shrink label, and it is preferable to use a thermoplastic resin film that shrinks by heat treatment. In particular, it is preferable to use a heat-shrinkable thermoplastic resin film (called a heat-shrinkable film) that has high mechanical and chemical strength and good printability. Examples of such heat-shrinkable films include oriented polyester films, shrinkable polyvinyl chloride films, shrinkable polystyrene films, shrinkable polyethylene terephthalate films, and shrinkable polypropylene films. The surface to be printed may be untreated or may be subjected to surface treatment such as plasma treatment, corona treatment, radiation treatment, and silane coupling treatment. The thermoplastic resin film may have a single layer structure or a multilayer structure. Furthermore, the thermoplastic resin film may be subjected to aluminum vapor deposition or transparent vapor deposition.

[0058] In this embodiment, a printed matter is obtained by printing the aqueous ink on a substrate and providing a printed layer. In this regard, the ink is usually applied to the substrate using a printing method such as gravure printing or flexographic printing, and the ink is dried and fixed in an oven to obtain a printed layer. The drying temperature is usually about 40 to 60°C.

[0059] The thickness of the printed layer of the above-mentioned water-based ink is not particularly limited, and can be appropriately determined taking into account various factors such as the ink drying properties when forming the printed layer and running costs.

[0060] The above-mentioned water-based ink printing layer is preferably formed using a printing method such as flexographic printing or gravure printing. Both flexographic printing and gravure printing are types of rotary printing, and can form a printing layer that maintains the five characteristics well. In addition, flexographic printing and gravure printing are preferable in terms of high-speed printing suitability, print reproducibility, etc.

[0061] Flexographic printing is a type of letterpress printing that mainly uses a rubber plate as the printing plate (relief plate) and a fine mesh engraved roll called an anilox roll to supply ink to the plate. The anilox roll receives ink from a chamber-type doctor and applies ink onto the printing plate, and has the advantage that the ink can be transferred evenly to the printing plate by passing it through the anilox roll.

[0062] Specifically, ink is applied to the surface of an anilox roll, which has partitions and many openings surrounded by the partitions, and a doctor is pressed against the surface of the anilox roll to scrape off the ink present on the top surfaces of the partitions of the anilox roll and fill the recesses, which are the openings, with ink. Next, a flexographic plate is pressed against the anilox roll to transfer the ink present in the recesses of the anilox roll to the raised parts (pattern parts) of the printing plate, and then the plate is brought into contact with a substrate to transfer the ink present in the pattern parts of the plate to the substrate, thereby obtaining a printed matter.

[0063] Rotary printing methods may also be combined. For example, when rotary printing is performed using a thermoplastic resin film as the substrate, rotary printing is performed using water-based ink on the surface of a rolled thermoplastic resin film. After printing, processes such as lamination, slitting (cutting off unnecessary width portions), and bag making (cutting out and heat sealing to make bags) can be performed. Rotary printing of water-based ink on a rolled thermoplastic resin film allows high-speed printing and is highly productive.

[0064] As described above, rotary printing includes gravure printing and flexographic printing, and either method can be used. However, it is preferable to use the flexographic printing method for printing the water-based ink of the present invention. Therefore, flexographic printing will be described in detail below. In this specification, rotary printing refers to gravure printing and flexographic printing, and does not include other printing methods such as ink jet printing and silk screen printing.

[0065] In flexographic printing, water-based ink is supplied from a container to an anilox roller having an uneven surface, either directly or via an ink supply pump or the like. The water-based ink supplied to the anilox roller is transferred to the plate surface upon contact with the raised portions of the plate surface, and is then finally transferred to the thermoplastic resin film upon contact between the plate surface and the thermoplastic resin film, forming a pattern and / or letters.

[0066] When using water-based ink, the ink drying property is slightly inferior to that of solvent-based flexographic printing ink, so it is preferable that the ink film thickness is as thin as possible. From this viewpoint, it is preferable that the amount of ink supplied to the Aronix roller is as small as possible. On the other hand, since the print density tends to decrease as the film thickness decreases, it is preferable to appropriately control the pigment concentration in the water-based ink used. Specifically, the appropriate print density can be obtained when the pigment concentration in the water-based ink is 1 to 5% higher by weight than the concentration of the solvent-based flexographic printing ink.

[0067] The term "wound thermoplastic resin film" refers to a roll of thermoplastic resin film aligned to a specified width, and is a film for rotary printing, which is different from sheets of paper that are cut off one by one in advance. The width of the film is appropriately selected based on the plate width of the rotary printing press to be used and the width of the image (picture) part of the gravure plate. When using multiple colors of rotary printing inks to overlay colors, the order of printing is not particularly limited.

[0068] When performing surface printing, it is common to print white ink first and then print colored inks as necessary. When multiple colored inks are used, they can be printed in the order of, for example, yellow, magenta, cyan, and black, but this is not particularly limited. In the case of surface printing, the water-based ink of the present invention is applied as an overcoat to the printing surface of a web-printed product.

[0069] When the color of the substrate is white, that is, for example, when the substrate is a paper substrate or a thermoplastic resin film having a white pigment kneaded therein, printing using only colored inks is possible as necessary.

[0070] In addition, when reverse printing is performed, it is common to first print color inks on a rolled thermoplastic resin film, and then print white ink. When multiple color inks are used, they can be printed in the order of, for example, black, cyan, magenta, and yellow, but this is not particularly limited. In addition to the above basic colors, large-scale printing machines can also use special colors. That is, large-scale printing machines have multiple printing units corresponding to 5 to 10 colors, each printing unit is equipped with one color of ink, and 5 to 10 colors can be printed at once. The printed matter obtained by reverse printing can be used as it is, or an anchor coating agent and an adhesive can be applied to the printed surface of the obtained rotary printed matter, and after drying as necessary, it can be laminated with a film or the like.

[0071] The ink layer (printed layer) in the laminate of the present invention has a tough film property that can withstand contact with the outside, and has excellent blocking resistance and water friction resistance, so it can be used as a layer located on the outermost surface. In that case, the laminate of the present invention may further include an intermediate ink layer between the substrate and the ink layer. Such an intermediate ink layer can be a printed layer of any ink, and may be only one layer or may be two or more layers. In addition, the intermediate ink layer may be a colored ink layer that appropriately contains a color material such as a pigment based on the desired design. The ink layer (printed layer) in the laminate of the present invention is also preferably used as a colored ink layer because it has excellent pigment dispersibility even in a composition containing a pigment, and has excellent adhesion, blocking resistance, and film properties. In particular, by using it as a white ink layer containing a high concentration of pigment, an ink layer with excellent cosmetic properties can be obtained by one printing. The manufacturing method of the intermediate ink layer is not particularly limited, and it can be manufactured in the same manner as the printing layer of the water-based ink of the present invention described above.

[0072] The laminate of the present invention has excellent adhesion to any type of substrate including plastic film, and in addition to the physical properties described in the examples, it also has excellent coating strength, particularly abrasion resistance and scratch resistance, so it is suitable for a form in which the printed layer is the outermost layer. Therefore, in front-printed printed matter or back-printed printed matter, a printed matter having a printed layer of the water-based ink of the present invention on the surface that will be the outermost layer during distribution is preferred because it can maximize the effects of the present invention. The laminate of the present invention can be used in a variety of applications, such as plastic labels (such as shrink labels and wrap-around labels) for beverage or food bottles, integrated packages, exterior packages, etc. In particular, the laminate of the present invention is suitably used as a heat shrinkable film in the various applications described above. EXAMPLES

[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the examples, "parts" and "%" refer to "parts by mass" and "% by mass", respectively.

[0074] [Self-crosslinking (meth)acrylic resin emulsion Resin A] A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux tube was charged with 60.0 parts by mass of n-propyl acetate. The mixture was heated to 90°C while stirring under a nitrogen atmosphere. Meanwhile, 57.0 parts by mass of methyl methacrylate, 10.0 parts by mass of n-butyl methacrylate, 13.0 parts by mass of n-butyl acrylate, 20.0 parts by mass of methacrylic acid, and 1.0 parts by mass of azobisisobutyronitrile were dissolved in 40.0 parts by mass of n-propyl acetate and dropped using a dropping funnel over 4 hours. After the dropwise addition was completed, the reaction was continued for another 6 hours. After the reaction was completed, the mixture was cooled, and 8.0 parts by mass of 30% ammonia water was added to the obtained acrylic resin solution to neutralize it. Furthermore, ion-exchanged water was added and the solvent was replaced while heating, to obtain an aqueous solution of acrylic resin with a solid content of 55%. The above resin had an acid value of 130 mgKOH / g and a Tg of 83°C. Then, 32.1 parts by mass of the above acrylic resin aqueous solution was charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux tube, and 160.0 parts by mass of ion-exchanged water was added. The temperature was raised to 75°C while stirring under a nitrogen atmosphere. Next, using a dropping funnel, 33.0 parts by mass of methyl methacrylate, 31.0 parts by mass of n-butyl methacrylate, 32.0 parts by mass of n-butyl acrylate, 4.0 parts by mass of diacetone acrylamide, and 3.5 parts by mass of 30% ammonium persulfate were dropped over 4 hours. After the dropwise addition was completed, the reaction was continued for another 6 hours. Then, 3 parts by mass of adipic acid dihydrazide (ADH) was added to the obtained acrylic emulsion solution to obtain a self-crosslinking (meth)acrylic resin emulsion (resin A) with a solid content of 40%. Resin A had an acid value of 20 mgKOH / g and a Tg of 33°C.

[0075] [Acrylic resin emulsion Resin EM] A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux tube was charged with 60.0 parts by mass of n-propyl acetate. The temperature was raised to 90°C while stirring under a nitrogen atmosphere. Meanwhile, 10.0 parts by mass of methyl methacrylate, 59.0 parts by mass of styrene, 5.0 parts by mass of 2-ethylhexyl acrylate, 26.0 parts by mass of acrylic acid, and 1.0 parts by mass of azobisisobutyronitrile were dissolved in 40.0 parts by mass of n-propyl acetate and dropped using a dropping funnel over 4 hours. After the dropwise addition was completed, the reaction was continued for another 6 hours. After the reaction was completed, the mixture was cooled, and 8.0 parts by mass of 30% ammonia water was added to the obtained acrylic resin solution to neutralize it. Furthermore, ion-exchanged water was added and the solvent was replaced while heating, and an aqueous solution of acrylic resin with a solid content of 55% was obtained. The above resin had an acid value of 202 mgKOH / g and a Tg of 94°C. Then, 182.8 parts by mass of the above acrylic resin aqueous solution was charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux tube, and 220.0 parts by mass of ion-exchanged water was added. The temperature was raised to 75°C while stirring under a nitrogen atmosphere. Next, using a dropping funnel, 10.0 parts by mass of methyl methacrylate, 41.0 parts by mass of styrene, 49.0 parts by mass of 2-ethylhexyl acrylate, and 3.5 parts by mass of 30% ammonium persulfate were dropped over 4 hours. After the dropping was completed, the reaction was continued for another 6 hours to obtain an acrylic resin emulsion (resin EM) with a solid content of 40%. The resin EM had an acid value of 101 mgKOH / g and a Tg of 52°C.

[0076] [Alkali-soluble water-soluble resin Resin a] A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, and a reflux tube was charged with 80.0 parts by mass of methyl triglycol. The temperature was raised to 90°C while stirring under a nitrogen atmosphere. Next, using two dropping funnels, 46.0 parts of styrene, 5.0 parts of methyl methacrylate, 20.0 parts of n-butyl methacrylate, and 29.0 parts of methacrylic acid were dropped from one of them over 4 hours. From the other, 5.0 parts of azobisisobutyronitrile were dissolved in 10.0 parts of methyl isobutyl ketone and dropped over 4.5 hours. After the dropwise addition, the reaction was continued for another 4 hours. After the reaction was completed, the mixture was cooled, and 10.0 parts by mass of 30% ammonia water was added to 55 parts of the obtained acrylic resin solution to neutralize it. Furthermore, ion-exchanged water was added and the solvent was replaced while heating, and an acrylic-soluble water-soluble resin with a solid content of 30% was obtained. Resin a had an acid value of 189 mgKOH / g and a Tg of 94°C.

[0077] [Alkali-soluble water-soluble resin Resin b] The alkali-soluble water-soluble resin (resin b) was prepared by the same procedure as in the preparation of the alkali-soluble water-soluble resin (resin a) described above, but with appropriate changes to the conditions so that the acid value was 215 mg KOH / g, the Tg was 110°C, and the solid content was 30%.

[0078] [Alkali-soluble water-soluble resin Resin c] The alkali-soluble water-soluble resin (resin c) was prepared by the same procedure as in the preparation of the alkali-soluble water-soluble resin (resin a) described above, but with appropriate changes to the conditions so that the acid value was 241 mgKOH / g, the Tg was 104°C, and the solid content was 30%.

[0079] [Preparation of Water-Based Ink and Laminate] In each example, a water-based ink was prepared according to the formulation shown in the table in a conventional manner. On the other hand, a corona-treated polystyrene heat-shrinkable film (Bonset BS55S, 50 μm thick, manufactured by Takiron CI Co., Ltd.) was prepared as a substrate, and a Flexoproof100 test printing machine (200 lines / inch anilox, manufactured by Testing Machines, Inc.) was prepared as a printing device. Then, using the anilox roll and resin plate of this test printing machine, a solid pattern of 240 mm length x 80 mm width was printed with the water-based ink of each example at a printing speed of 100 m / min. Next, the obtained print was aged at 25° C. for 24 hours to obtain a printed ink laminate.

[0080] The obtained laminate was evaluated as follows.

[0081] (Pigment Dispersibility) The ink was adjusted to a liquid temperature of 25° C. on the day after preparation, and the viscosity was measured using a Zahn cup #4 for evaluation. Within 5:20 seconds 4:20 seconds - within 30 seconds Within 3:30 seconds-40 seconds Within 2:40-50 seconds 1:50+ seconds

[0082] (Adhesion to substrate) Cellophane tape was applied to the surface of the laminate on which the ink layer was formed. The cellophane tape was then quickly peeled off, and the degree of peeling of the ink layer (film) from the substrate was visually observed and evaluated according to the following criteria. The evaluation result of 4.5 was when evaluation results of 4 and 5 were mixed at the same level among multiple evaluations. The practical level is 4 or higher. 5: No peeling of the ink layer 4: The area of ​​the ink layer peeling is more than 0% but less than 10% of the printed area. 3: The area of ​​the ink layer peeling off is between 10% and 30% of the printed area 2: The area of ​​the ink layer peeling off is between 30% and 75% of the printed area 1: The ink layer peels off over 75% of the printed area.

[0083] (Blocking resistance) The printed surface of the laminate is 5kg / cm2. 2 The test piece was left to stand for one day at 40°C and 80% humidity under a load of 100 g / m2.Then, the test piece was peeled off by hand, and the presence or absence of peeling resistance and the degree of transfer of the ink layer (film) were visually observed and evaluated according to the following criteria. 5: No ink layer transfer, no peeling resistance 4: No ink transfer, but resistant to peeling 3: The amount of ink layer transferred is less than 10% of the printed area, and there is peeling resistance. 2: The amount of ink layer transferred is between 10% and 50% of the printed area, and there is peeling resistance. 1: The ink layer transfers to 50% or more of the printing area and has peel resistance

[0084] (Alcohol resistance) A 50 μm drop of ethanol was applied to the printed surface as an evaluation solution, and after drying at room temperature for 24 hours, the coating film was washed with water at room temperature and the degree of peeling and whitening of the coating film was evaluated. 5: No change in appearance 4: Slightly whitened 3: Whitening present 2: Slight ink detachment 1: Ink detachment occurs

[0085] (Water friction resistance) The surface of the laminate on which the ink layer was formed was rubbed with a water-soaked Kanakin, and rubbed 100 times with a load of 200 g using a Gakushin-type rub fastness tester. The degree of peeling of the ink layer (film) was then visually observed and evaluated according to the following criteria. 5: No peeling of the ink layer 4: The area of ​​the ink layer peeling is more than 0% but less than 10% of the printed area. 3: The area of ​​the ink layer peeling off is between 10% and 50% of the printed area 2: The area of ​​the ink layer peeling off is between 50% and 70% of the printed area 1: The area of ​​the ink layer that has peeled off is 70% or more of the printed area.

[0086] (white density) The white density of the prints was evaluated using a transmission densitometer. 5:0.2 or more 4:0.16 or better 3:0.12 or higher 2:0.1 or more 1:0.1 or less

[0087] (Ink washability) Thirty minutes after the ink was applied, a synthetic detergent was applied to the coating, and the coating was wiped with a cloth to evaluate the peeled area. 5: Peeling area 100% 4: Peeling area is less than 50-100% 3: Peeling area less than 10-50% 2: Peeling area less than 1-10% 1: No peeling

[0088] The results are shown in Tables 1 to 3. In the tables, the numbers in the "mixture" column indicate the mass % of the solid content other than the solvent.

[0089] [Table 1]

[0090] [Table 2]

[0091] [Table 3]

[0092] Details of each component other than the resin in the table are as follows. Solvent: Ion-exchanged water Surfactant: alkylene oxide modified acetylene glycol surfactant (Surfynol 420, manufactured by Nissin Chemical Industry Co., Ltd.) Color pigment: Titanium oxide made by Teika Corporation "TITANIX JR-701" Wax: Polyethylene wax (Chemipearl W-400, manufactured by Mitsui Chemicals, Inc.) Antifoaming agent: Silicone emulsion (TEGO Foamex 1488 manufactured by Evonik) Silicone additive: Silicone emulsion (TEGO Glide490 manufactured by Evonik) Aziridine compound: Aziridine-based curing agent ("PZ-33" manufactured by Nippon Shokubai Co., Ltd., NV value: 100% by mass) Epoxy: Epoxy hardener (EX-614B manufactured by Nagase Chemtex Corporation) Isocyanate: Isocyanate-based hardener (Mitsui Chemicals Takenate WD-726) Carbodiimide: Carbodiimide-based curing agent (Carbodilite E-02, manufactured by Nisshinbo Co., Ltd.) Titanium chelate: Titanium chelate-based hardener (TC-300, manufactured by Matsumoto Fine Chemical Co., Ltd.)

[0093] As can be seen from each table, the examples according to the present invention received good evaluation results in all of the substrate adhesion, blocking resistance, alcohol resistance, and water friction resistance, and are excellent in various durability properties in addition to adhesion to the substrate. Furthermore, even in inks containing high concentrations of pigment, it exhibits excellent pigment dispersibility, adhesion to the substrate, and various types of durability.

Claims

1. The binder resin contains a binder resin, a curing agent, and an aqueous solvent, and the binder resin contains a self-crosslinking (meth)acrylic resin emulsion and an alkali-soluble water-soluble resin, the alkali-soluble water-soluble resin is an acrylic resin or a styrene-acrylic resin, The acid value of the alkali-soluble water-soluble resin is 40 mgKOH / g to 250 mgKOH; The glass transition temperature (Tg) of the alkali-soluble water-soluble resin is 10° C. to 140° C. Water-based ink.

2. 2. The water-based ink according to claim 1, wherein the hardener is an aziridine-based hardener.

3. 3. The water-based ink according to claim 1, wherein at least one of the self-crosslinking (meth)acrylic resin emulsion and the alkali-soluble water-soluble resin contains a styrene-acrylic resin.

4. 3. The water-based ink according to claim 1, wherein a mass ratio of the non-volatile content of the self-crosslinking (meth)acrylic resin emulsion to the alkali-soluble water-soluble resin is self-crosslinking (meth)acrylic resin emulsion / alkali-soluble water-soluble resin=10 / 90 to 90 / 10.

5. An aqueous ink as described in claim 1 or 2, wherein the ratio of the self-crosslinking (meth)acrylic resin emulsion and the alkali-soluble water-soluble resin in the binder resin is 70 mass% or more.

6. 3. The water-based ink according to claim 1, wherein the acid value of the self-crosslinking (meth)acrylic resin emulsion is from 0 mgKOH / g to 100 mgKOH / g.

7. The water-based ink according to claim 1 or 2, further comprising a pigment.

8. 8. The water-based ink according to claim 7, wherein the pigment is titanium oxide, and the content of the pigment in the water-based ink is 30% by mass or more.

9. 3. The water-based ink according to claim 1, which is used for flexographic printing or gravure printing.

10. A laminate comprising a substrate and a printed layer provided on the substrate, the printed layer being a printed layer of the water-based ink according to claim 1 or 2.

11. The laminate according to claim 10, comprising a layer of varnish on the printed layer.

Citation Information

Patent Citations

  • JP07441356B

  • New xylanase compositions and methods for their production

    JP2000501935A

  • Water-based screen printing ink

    JP2005518459A

  • Pigment preparation in granular form

    JP2013100533A

  • Water-based ink with high renewable content

    JP2020531606A